Hypericum - Fior, Manuele (Fantagraphics Books, Inc., 2023)
"Teresa's life has always been a comfortable straight line, with every goal set for herself achieved right on schedule. It comes as little surprise when she wins a prestigious scholarship to help mount an exhibition in Berlin celebrating the discovery of Tutankhamen's tomb by Howard Carter in 1922. Ruben is a fellow young Italian who never finished his art studies and views Berlin as his personal playground. When Teresa and Ruben meet, fate will forever change the trajectory of their existence. Hypericum follows, in parallel, Carter's landmark 1920s discovery in Egypt and Teresa and Ruben's passionate yet tormented love affair, set in 1990s Berlin. Between Egypt and Berlin, the two eras confront and intertwine in a story that has at its center the hypericum, or St. John's wort, a plant with unusual properties... This sublimely romantic journey into Egyptian grandeur, the vibrations of youth, and the anxieties of the heart is a masterpiece of graphic fiction by one of the world's great contemporary graphic novelists, about how the strongest bonds are created by the passage of time."--Amazon.com.